Edukasi Pemanfaatan dan Praktik Pengolahan Pangan Budidaya Lokal Sebagai Upaya Pencegahan Stunting di Provinsi Aceh: Education on the Utilization and Practice of Locally Cultivated Food Processing as an Effort to Prevent Stunting in Aceh Province - Pakpahan, Novriaman; Yuliani, Hilka; Rasyid, Maya Indra; Maryati, Sri; Husin, Hasanuddin; Angraeni, Lia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Aceh Province is one of district that has a very high stunting prevalence rate in Indonesia. Community service activities was aimed to provide knowledge and public awareness of the importance of the health of pregnant women and children as an effort to prevent stunting. Community service activities also carried out food processing practices aimed at providing community skills in processing food as nutritious food intake for mothers and children. The target participants of the community service activities are villagers, village apparatus and posyandu officials. The total number of participants who took part in the community service activities was 120 participants consisting of 35 men and 85 women. Meanwhile, based on the group of participants, it consisted of 101 villagers, 12 village officials and 7 posyandu delegation. Based on evaluation, the activity succeeded in providing understanding and awareness of the community regarding the importance of food intake for the health of mothers and children and also succeeded in increasing the participants' skills in processing several nutritious processed food products. Furthermore, the assessment of the results of the written test showed that the average participant obtained a fairly good score. It shows that the participants understand the learning material quite well. However, the ability to answer the written test can be improved by repeating reading the learning module. Guidance from stakeholders towards villagers on an ongoing basis needs to be programmed in order to have a wider positive impact.